How to promote sustainable land use in Hangzhou Bay, China? A decision framework based on fuzzy multiobjective optimization and spatial simulation - Zhang, Tao; Xin, Xu; He, Fang; Wang, Xiaoli; Chen, Kang (Journal of cleaner production, 2023)
Rapid economic development has a significant impact on both regional land use/cover change (LUCC) and ecosystem services. In this paper, we present a decision framework based on fuzzy multiobjective optimization and spatial simulation to achieve sustainable land use development. Specifically, we first investigate the evolution of LUCC in Hangzhou Bay, China, and assess its ecosystem service value (ESV) using the equivalence coefficient table method based on land use data in 2000, 2010 and 2020. Then, we construct a multiobjective fuzzy linear programming model to optimize the land use decision that can balance the ESV and economic benefits of the land. Finally, a future land use simulation model is established to perform spatial simulation to find the most likely land use scenario for Hangzhou Bay in 2030 using the optimization results as input. Our results show that the LUCC in Hangzhou Bay became more frequent between 2000 and 2020, especially the area of built-up land, which increased by 179.74%. The ESV in Hangzhou Bay shows an accelerated decreasing trend, with a total decrease of 1.22 × 108 yuan. We observe spatial heterogeneity in both LUCC and ESV in Hangzhou Bay, with LUCC occurring more frequently in the coastal area, while high ESV areas are concentrated in the eastern coastal area and southern forest. The land use decisions obtained through land use structure optimization and spatial simulation can significantly slow down the decreasing trend of ESV (from −14.5% to −0.17%), effectively reduce the fragmentation of the landscape, prevent the disorder of LUCC, and help the government formulate sustainable land use policies. [Display omitted] •The ecological service values (ESVs) of Hangzhou Bay are assessed from 2000 to 2020.•The characteristics of land use/cover change (LUCC) and ESVs are analyzed.•A bi-objective fuzzy linear programming is developed to optimize the land use structure.•Simulations of LUCC and ESV in 2030 are conducted based on the optimization result.•Optimization and spatial simulation balance ecological and economic benefits of land.